2000
DOI: 10.1021/jf990956x
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Phytotransformation of o,p‘-DDT and p,p‘-DDT by Axenically Cultivated Aquatic Plants

Abstract: The uptake and phytotransformation of o,p'-DDT and p,p'-DDT were investigated in vitro using three axenically cultivated aquatic plants: parrot feather (Myriophyllum aquaticum), duckweed (Spirodela oligorrhiza), and elodea (Elodea canadensis). The decay profile of DDT from the aqueous culture medium followed first-order kinetics for all three plants. During the 6-day incubation period, almost all of the DDT was removed from the medium, and most of it accumulated in or was transformed by these plants. Duckweed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 34 publications
(43 reference statements)
2
34
0
1
Order By: Relevance
“…For example, Elodea could be sorbing malathion onto its surfaces and thus reducing water toxicity to Daphnia. However, although many highly-lipophilic insecticides with Log K OW values greater than 6.0 (e.g., pyrethroid and organochlorine insecticides) will bind rapidly to submersed macrophytes [20,21], malathion is relatively hydrophilic (Log K OW ¼ 2.3), and it remains unclear how much macrophytes will sorb this insecticide. In the aforementioned experiment by Gao et al [23], the authors found no evidence that malathion was taken up by macrophytes during the first 48 h following exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Elodea could be sorbing malathion onto its surfaces and thus reducing water toxicity to Daphnia. However, although many highly-lipophilic insecticides with Log K OW values greater than 6.0 (e.g., pyrethroid and organochlorine insecticides) will bind rapidly to submersed macrophytes [20,21], malathion is relatively hydrophilic (Log K OW ¼ 2.3), and it remains unclear how much macrophytes will sorb this insecticide. In the aforementioned experiment by Gao et al [23], the authors found no evidence that malathion was taken up by macrophytes during the first 48 h following exposure.…”
Section: Discussionmentioning
confidence: 99%
“…For example, macrophytes can sorb insecticides, potentially reducing the duration and intensity of exposure experienced by aquatic taxa [18,19]. In fact, submersed macrophytes can sorb up to 90% of insecticides from the water column within 24 h, but such high sorption rates only occur for highly lipophilic compounds (i.e., Log octanolwater partition coefficient, K OW > 6.0), such as organochlorine (e.g., dichlorodiphenyltrichloroethane [DDT]) and pyrethroid (e.g., lambda-cyhalothrin) insecticides [20,21]. For less lipophilic compounds-such as the commonly applied organophosphate insecticides chlorpyrifos (Log K OW ¼ 4.81) and malathion (Log K OW ¼ 2.3)-the amount of insecticides removed from the water column by macrophytes typically ranges from 0 to 50% in a 24-h period [18,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…After 0, 3,8,11,15,21, and 29 d of continuous irradiation, duplicate vessels (one from each radiolabel position) were removed for analysis. The radioactivity in each aqueous sample and its corresponding NaOH trap was quantified by LSC to determine the mass balance, and each aqueous sample was analyzed by HPLC to determine the levels of isopyrazam and significant photodegradation products present at each timepoint.…”
Section: Direct Photolysis Study Designmentioning
confidence: 99%
“…There are a number of studies reporting on phytoremediation [16] and bioremediation [17] of DDT. Reductive catalytic methods have been also reported, e.g.…”
Section: Introductionmentioning
confidence: 99%